Cytokeratin 18‐based cell death markers indicate severity of liver disease and prognosis of cirrhotic patients. (4th April 2016) - Waidmann, Oliver; Brunner, Friederike; Herrmann, Eva; Zeuzem, Stefan; Piiper, Albrecht; Kronenberger, Bernd
Abstract: Background & Aims: Hepatocyte death is an important factor in development and progression of cirrhosis. Cytokeratin 18‐based serum markers reflecting apoptotic (M30) and overall epithelial cell death (M65 and M65EpiDeath) have been used as prognostic parameters for survival in patients with acute liver failure. However, there has been no trial investigating M30, M65 and M65EpiDeath as survival parameters in patients with cirrhosis and acute‐on‐chronic liver failure. Methods: Patients with cirrhosis were enrolled and followed until death, liver transplantation or last contact. M30, M65 and M65EpiDeath serum levels were quantified in patient's sera. Results: Three hundred and thirty‐one patients were screened and 211 patients could be included in this study. The median duration of follow‐up was 322 days with a range of 1–1382 days. All three cell death parameters correlated with the extent of the severity of the disease. However, M65EpiDeath was the only of the three parameters which was associated with the severe complications of cirrhosis including ascites, spontaneous bacterial peritonitis and hepatorenal syndrome. Additionally, M65EpiDeath was the only cell death parameter which was independently from liver function and its surrogate parameter such as Child‐Pugh score and the model of end‐stage liver disease associated with overall survival. Conclusions: Epithelial cell death reflected by M65EpiDeath serum levels is an indicator for the severity of cirrhosis and a prognostic survival parameter in cirrhotic patients.